Towards an Educational Computer Architecture for the University of Khartoum - Abdelrahman Ali, Mohammed; Salah Ahmed, Omer; Bedri, Abdelkareem; F. Babiker, Sharief (University of Khartoum Engineering Journal, 2022)
Computer science and architecture is one of the fastest growing areas of knowledge and is being intensely studied and researched. In the last few years, many new computer architectures were introduced by the computer industry. Also, many academic institutions and universities have developed their own architectures for educational purposes and continued to advance their architectures through ongoing research and educational projects. This paper reports on the first Sudanese computer architecture that has been designed and implemented at the University of Khartoum. This computer is a general purpose computer that executes one program at a time without pipelining. A reduced instruction set has been chosen such that the UofK computer would have the same executing power as any other computer with a full instruction set. The instruction manipulations include arithmetic, logical, data transfer together with branching operations. The architecture provides for program input facilities, data input and output functions. The architecture behaviour was described using VHDL. The VHDL code was then used to implement the design in a Field Programmable Gate Array to obtain a full functioning prototype. The computer has been successfully tested using sample programs. This implementation is considered an important step towards building an educational computer architecture infrastructure for the University of Khartoum and other Sudanese universities.